Impact of low‐intensity pulsed ultrasound on the growth of Schizochytrium sp. for omega‐3 production. Issue 1 (13th October 2020) - Savchenko, Oleksandra; Xing, Jida; Burrell, Mark; Burrell, Robert; Chen, Jie
Abstract: Schizochytrium sp . is a microalga that is known for its high content of oils or lipids. It has a high percentage of polyunsaturated fatty acids in the accumulated oil, especially docosahexaenoic acid (DHA). DHA is an important additive for the human diet. Large‐scale production of Schizochytrium sp . can serve as an alternative source of DHA for humans as well as for fish feed, decreasing the burden on aqua systems. Therefore, research on improving the productivity of Schizochytrium attracts a lot of attention. We studied the potential of using low‐intensity pulsed ultrasound (LIPUS) in the growth cycle of Schizochytrium sp . in shake flasks. Different intensities and treatment durations were tested. A positive effect of LIPUS on biomass accumulation was observed in the Schizochytrium sp . culture. Specifically, LIPUS stimulation at the ultrasound intensity of 400 mW/cm 2 with 20 min per treatment 10 times a day with equal intervals of 2.4 h between the treatments was found to enhance the growth of Schizochytrium biomass most effectively (by up to 20%). Due to the nature of cell division in S chizochytrium sp . which occurs via zoospore formation, LIPUS stimulation was inefficient if applied continuously during all 5 days of the growth cycle. Using microscopy, we studied the interval between zoospore formation in the culture and selected the optimal LIPUS application days (Days 0–1 and Days 4–5 of the 5‐day growth cycle). Microscopic images have also shown that LIPUS stimulation enhances zoospore formation in Schizochytrium sp ., leading to more active cell division in the culture. This study shows that LIPUS can serve as an additional tool for cost‐efficiency improvement in the large‐scale production of Schizochytrium as a sustainable and environmentally friendly source of omega‐3 (DHA). Abstract : Effect of the low intensity pulsed ultrasound on cultivation of Schitzochytrium sp . for DHA production was described. Savchenko et al. showed that LIPUS could be a promising new tool to enhance the yield and productivity of the bioprocess and reduce the cost. The authors studied how parameters such as intensity of ultrasound, continuity of stimulation, cell division intervals and culture growth phase can impact the final result of the microbial bioprocess.